FAKTOR-FAKTOR YANG MEMENGARUH KINERJA PERUSAHAAN MANUFAKTUR - Angelia, Christy; Sha, Thio Lie (Jurnal Paradigma Akuntansi, 2023)
This study aims to obtain empirical evidence about the impact of liquidity, leverage, firm age, and intangible assets on firm performance. The subjects used in this study were manufacturing companies listed on the Indonesian Stock Exchange during 2018-2020 period with a sample of 78 companies with 234 data. Data processing using Eviews 11 software with purposive sampling method. The results of this study shows firm age has a negative significant effect and leverage has a positive significant effect on firm performance. While liquidity and intangible assets have a positive insignificant effect on firm performance. The implication of this research is that companies need management that is able to manage their companies well so that they can improve the firm's performance to carry on and survive in the competition.